I don't quite get a problem. I've got an inequality:
0 < ab < ac
(1) -> c < 0 -> this one I understand well
(2) -> b > c
Is "a" negative?
I know that ab and ac > 0, ab < ac
b could be bigger than c and still ab < ac when b is negative but then the expression will not be bigger than 0. If "a" alone is negative also the whole expression will not be bigger than 0.
If a is negative and b is negative then ab will not be < ac.
I don't quite get it. Pls help
We are given 0<ab<ac
=> ab and ac both are positive.
Statement 1: c <0
=> for ac to be positive , a must be negative. Sufficient
Statement 2: b >c
Now lets take a look at what is given in question
=> ab <ac
=> ab-ac <0
=> a(b-c) <0
But from statement 2 we know b>c thus b-c must be positive.
Therefore for a(b-c) <0 to be true, a must be negative. Sufficient.
Since each statement is sufficient, Ans D it is.
Hope it helps.
Black Friday Debrief